Effect of dissolved solids released from biochar on soil microbial metabolism. Issue 4 (25th March 2022) - Hu, Jiajun; Tang, Han; Wang, Ya Zhu; Yang, Chen; Gao, Min-tian; Tsang, Yiu Fai; Li, Jixiang
Abstract : Dissolved solids released from biochar could redistribute the metabolic flux of soil microorganisms. Abstract : Dissolved solids released from biochar (DSRB), including organic and inorganic compounds, may affect the role of biochar as a soil amendment. In this study, the effects of DSRB on soil microbe metabolism, especially CO2 fixation, were evaluated in liquid soil extract. DSRB were found to be released in large amounts (289.05 mg L −1 at 1 hour) from biochar over a short period of time before their rate of release slowed to a gradual pace. They increased the microbial biomass and provided energy and reducing power to microbes, while reducing their metabolic output of extracellular proteins and polysaccharides. DSRB inputs led to the redistribution of metabolic flux in soil microorganisms and an increased organic carbon content in the short term. This content gradually decreased as it was utilized. DSRB did not improve microbial CO2 fixation but, rather, enhanced its release, while promoting specific soil microorganism genera, including Cupriavidus, Flavisolibacter, and Pseudoxanthomonas . These heterotrophic genera may compete with autotrophic microorganisms for nutrients but have positive synergistic relationships with autotrophs during CO2 fixation. These results demonstrated that reducing the DSRB in biochar can improve its role as a soil amendment by enhancing soil carbon storage and CO2 fixation capabilities.